A realistic MIMO time-variant channel applied to diagonalizing precoders - Madi, G.; Vrigneau, B.; Pousset, Y.; Vauzelle, R. (2009 9th International Conference on ITS Telecommunications, 2009)
Precoders permits to enhance the performance of MIMO systems by optimizing a pertinent criterion of the transmission. For example, the max-d min precoder optimizes the minimum Euclidean distance of the received constellation. In this paper, we evaluate the performance of max-d min in a realistic time-variant channel for both spectral efficiency (4 and 8 bit/s/Hz). The channel is obtained by a 3D Propagation Simulation Software based on a raytracing method. Moreover, the speed effect is introduced by using the Jakes' model. We are able to obtain the temporal evolution of the channel and the statistics of key random variables. This permits us to study the max-d min precoder with a perfect channel state information and with a simple channel error estimation. The max-d min is also compared to the max-SNR precoder.